2014
DOI: 10.1007/s12033-014-9807-4
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Purification of Oligosaccharides from Copra Meal by Recombinant Endo-β-mannanase and Deciphering Molecular Mechanism Involved and Its Role as Potent Therapeutic Agent

Abstract: Production of manno-oligosaccharides (MOSs) from pretreated and defatted copra meal (dFCO) hydrolysis was achieved by endo-mannanase. Structural characterization of dFCO by FT-IR and NMR exhibited resemblance with galactomannan. The time-dependent hydrolysis of dFCO by recombinant endo-β-(1 → 4)-mannanase of Clostridium thermocellum by TLC and HPAEC displayed the release of mannose and MOSs mannobiose and mannotriose. Purified MOSs yielded 40 % mannobiose and 18 % mannotriose confirmed by mass spectroscopy whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 43 publications
6
47
0
Order By: Relevance
“…Apparently, 90% of the XOS will remain intact under the systemic factors influence for better performance as prebiotics. This result corroborated with the earlier report (34). The discrimination in growth promotion by mixed xylo-oligosaccharides of probiotic Lactobacillus and Bifidobacterium was due to the generation of short chain fatty acids and lactate from anaerobic fermentation in the presence of prebiotics that involved in supply energy for colonic epithelium and suppression of pathogenic intestinal bacteria by lowering of pH (35).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Apparently, 90% of the XOS will remain intact under the systemic factors influence for better performance as prebiotics. This result corroborated with the earlier report (34). The discrimination in growth promotion by mixed xylo-oligosaccharides of probiotic Lactobacillus and Bifidobacterium was due to the generation of short chain fatty acids and lactate from anaerobic fermentation in the presence of prebiotics that involved in supply energy for colonic epithelium and suppression of pathogenic intestinal bacteria by lowering of pH (35).…”
Section: Discussionsupporting
confidence: 94%
“…At low concentrations (300 μg/ml) of mixed XOS suppressed the proliferation of HT-29 and Caco-2 cells 90% and 75%, respectively, after 48 h. Such a finding can initiate the advancement of application of XOS of this kind in anticancer therapy and may pave the applications of XOS as nutraceutical and theragonostic implications as well. Earlier studies suggested that the fructooligosaccharides and manno-oligosaccharides from apple and coconut were effective against human colon cancer cell line due to cell cycle arrest in S phase leading to apoptosis (34, 54). Similar mechanisms might have enlighten in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations